An Overview of Noninvasive Brain Stimulation: Basic Principles and Clinical Applications - Bhattacharya, Amitabh; Mrudula, Kambhampati; Sreepada, Sai Sreevalli; Sathyaprabha, Talakad Narsappa; Pal, Pramod Kumar; Chen, Robert; Udupa, Kaviraja (Canadian journal of neurological sciences, 2022)
The brain has the innate ability to undergo neuronal plasticity, which refers to changes in its structure and functions in response to continued changes in the environment. Although these concepts are well established in animal slice preparation models, their application to a large number of human subjects could only be achieved using noninvasive brain stimulation (NIBS) techniques. In this review, we discuss the mechanisms of plasticity induction using NIBS techniques including transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS), transcranial alternating current stimulation (tACS), random noise stimulation (RNS), transcranial ultrasound stimulation (TUS), vagus nerve stimulation (VNS), and galvanic vestibular stimulation (GVS). We briefly introduce these techniques, explain the stimulation parameters and potential clinical implications. Although their mechanisms are different, all these NIBS techniques can be used to induce plasticity at the systems level, to examine the neurophysiology of brain circuits and have potential therapeutic use in psychiatric and neurological disorders. TMS is the most established technique for the treatment of brain disorders, and repetitive TMS is an approved treatment for medication-resistant depression. Although the data on the clinical utility of the other modes of stimulation are more limited, the electrical stimulation techniques (tDCS, tACS, RNS, VNS, GVS) have the advantage of lower cost, portability, applicability at home, and can readily be combined with training or rehabilitation. Further research is needed to expand the clinical utility of NIBS and test the combination of different modes of NIBS to optimize neuromodulation induced clinical benefits.